The Relationship of Parental Control with Children’s Digital Literacy Skills in Pesisir Selatan - Ismaniar Ismaniar; Klara Septia Landa (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The digital divide in Indonesia demands that digital literacy education be delivered through several knowledge transfer mechanisms. The purpose of this research is to look at the relationship between parental control and digital literacy skills in children in Pesisir Selatan. This type of research is quantitative correlational. Sources of data in this study are parents and children. The population in this study amounted to 30 parents and the sampling technique was Simple Random Sampling and 70% were taken, namely 21 children. The data collection method uses a questionnaire with a statement list format as a data collection tool, data analysis techniques use a percentage formula and to find correlations use the Rank Order formula. The results of the study found: 1) Parental control of this child was classified in the unfavorable category. 2) digital literacy skills in children are classified in the low category. 3) There is a significant relationship between parental control and digital literacy skills in children in Pesisir Selatan. Furthermore, some suggestions are: 1) According to the respondents' assessment, parental control over children is still much that has not been implemented, when viewed from the duties and responsibilities of parents, it is suggested to parents to better understand their duties and responsibilities so that they are able to protect children from the dangers of digital media. 2) It is necessary for children to be aware of how important it is to understand increasingly sophisticated digital media that can develop various potentials in children so that they have knowledge and experience. 3) It is hoped that other studies will be able to see several other factors that have not been studied in this study